The effect of Green Supply Chain Management Practices on Sustainable Performance, According to Egypt’s Vision 2030: A Case Study on ElSewedy Company - Elkhatib, Noha Nagy; Basiouny, Heba Mahmoud (The Arab Journal of Administration, 2025)
Purpose – This study aimes to investigate and determine the Effect of Green Supply Chain Practices (Green Procurement, Green Design, Internal Environmental Management, Green Manufacturing and Green Logistics) on Sustainable Performance, which was measured through the following dimensions (Environmental Performance, Social Performance and Economic Performance) at ElSewedy Company. Methodology – To achieve the objective of the study, researches relied on the descriptive analytical approach, where 47 surveys were distributed direct to Supply Chain Management Director, Operations Manager, Operations Coordinator, Warehouse Manager, Planning Director, Purchasing Manager, Purchasing coordinator, truck coordinator, and employees at the central Supply Chain Department at ELSewedy company. Descriptive analysis was applied to test the research hypothesis using SPSS v25 and Smart-pls v4. Findings –the results showed that there is a positive Effect of Green Supply Chain Management Practices on Sustainable Performance with a value of .839 in the targeted company. Recommendations- The researchers recommend that industrial organizations should use renewable and clean energy by reducing gas emissions, lowering energy consumption, minimizing waste and pollution, using gas instead of gasoline for transporting products, using clean energy in production, avoiding the usage of chemicals in production, and using electric vehicles for product transportation.